Binding of Anisoylated Lys-Plasminogen Streptokinase Activator Complex to Cells in Culture - Vasudevan, Jayanand; Humphries, John E; Gonias, Steven L (Thrombosis and Haemostasis, 1993)
Anisoylated Lys-plasminogen streptokinase activator complex (APSAC) was purified from Eminase® by chromatography on Superose-12. Purified APSAC did not significantly deacylate within 4 h at 4° C in solution as determined by hydrolysis of D-Val-L-leu-L-lys-p-nitroanilide HCl (S-2251). At 37° C, maximum amidase activity developed in 120 min; ε-amino-n-caproic acid (EACA) did not affect the apparent rate of APSAC deacylation but stabilized the streptokinase-plasmin(ogen) complex (SkPl) which formed. APSAC bound to C6 glioma cells and human umbilical vein endothelial cells (HUVECs) in culture. Binding was completely inhibited by EACA suggesting an essential role for the plasminogen kringle domains. Cell-associated APSAC deacylated to form active SkPl which hydrolyzed S-2251 and D-Val-Leu-Lys-7-amino-4-methyl coumarin. The rate of APSAC deacylation was increased when the APSAC was cell-associated. APSAC that was initially bound to C6 cells or HUVECs also activated 125I-plasminogen. This activity may have reflected cell-associated APSAC or APSAC that dissociated into solution. Plasmin was recovered bound to cells and in solution. These studies demonstrate that APSAC associates with cell-surfaces and retains activity. In the circulation, cell-surfaces may provide a significant pharmacologic compartment for intravenously administered APSAC.